If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10=-2(x-2)+6(x+1)
We simplify the equation to the form, which is simple to understand
10=-2(x-2)+6(x+1)
Reorder the terms in parentheses
10=+(-2x+4)+6*(x+1)
Remove unnecessary parentheses
+10=-2x+4+6+*(+x+1+)
Reorder the terms in parentheses
10=-2x+4+(+6x+6)
Remove unnecessary parentheses
+10=-2x+4+6x+6
We move all terms containing x to the left and all other terms to the right.
+2x-6x=+4+6-10
We simplify left and right side of the equation.
-4x=0
We divide both sides of the equation by -4 to get x.
x=-0
| 3.5x+7=7 | | 18-7y=-11 | | 2x^2+17x+8= | | -5(4b+2)+(21b-3)=0 | | 2x+x+2x+x=750 | | 20.3=t-(-3.9) | | 3(2t+5)+20= | | 5a(a+3)-a=4a-6+1 | | 40m^2-224=248m | | x+17+x+19-x=602 | | 15x-9x+5=20 | | 5.4-3.7-4.6=0.2-3.1 | | 3(y-4)+6(y+1)=57 | | (m+340)8=4256 | | 2x=15x^2 | | -4r-2(3r-8)=3r+1 | | 6x+48=8x-48 | | 17v/2=34/3 | | 12a^2-128a+256=0 | | 15.2=m-10.9 | | 5x-10(3x-6)=3(24-9x) | | -2(5y-1)+4y=4 | | 4x+7=3+2x | | -15.2=m-10.9 | | -15-2=m-10.9 | | ln(3x+4)=2.6 | | -5(2x+1)3x=37 | | 5x-11=x+21 | | n^2-7n-60= | | -25X^2+300=0 | | Ln(3x+4)=3.6 | | -8x-2=15 |